Trends in development assistance to new nenewable energy in sub-Saharan Africa - Rasmus Hundsbæk Pedersen; Ole Winckler Andersen; Henning Nøhr (Danish Institute for International Studies (DIIS), 2020)
Development assistance plays an important role in the development of energy sectors in sub-Saharan African countries and it is increasingly being used to promote new renewable energy like solar and wind. The relationship between aid and domestic African priorities is however complex and outcomes are not always as donors had intended. By way of collecting experiences from a number of different approaches in different African country contexts a new DIIS Working Paper analyses recent trends in development assistance for new renewable energy. Overall, the paper demonstrates a shift to promoting market-led approaches that aim at mobilising private capital for power-sector investments. Whereas more capital has indeed been mobilised for new renewable energy projects the paper suggests that more support is needed if a transition to cleaner energy and universal access to energy services are to be achieved. Furthermore, the promotion of market-led approaches poses not only opportunities, but also a number of challenges to governments and donors. Clean energy and decarbonisation are often less of a priority among key decision-makers in African countries than they are for western donors. The paper argues that it is important to recognise these different interests and to be realistic about how to bridge them. Furthermore, despite improvements in recent years the capacity to plan, procure and integrate renewable energy in power systems remains a challenge in many countries. This points to the importance of ensuring a balance between support for market development and support for capacity-building of government entities. Needs are likely to differ from one country to another and change as renewable technologies develop. The constant adaption of approaches is therefore crucial.
Keywords: 330; Erneuerbare Energie; Entwicklungshilfe; Subsahara-Afrika